2016
DOI: 10.3109/0284186x.2015.1120884
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists’ non-verbal behavior and analog patients’ recall of information

Abstract: Background Information in oncological consultations is often excessive. Those patients who better recall information are more satisfied, less anxious and more adherent. Optimal recall may be enhanced by the oncologist's non-verbal communication. We tested the influence of three nonverbal behaviors, i.e. eye contact, body posture and smiling, on patients' recall of information and perceived friendliness of the oncologist. Moreover, the influence of patient characteristics on recall was examined, both directly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Importantly, non-verbal communication can help recall information given in the consultation by the patient ( 51 ), which would improve therapy adherence and probably also reduce insecurity, fear, and anxiety in patients, and their relatives.…”
Section: Changes Due To Covid-19 Pandemic In Four Pillars Of Palliatimentioning
confidence: 99%
“…Importantly, non-verbal communication can help recall information given in the consultation by the patient ( 51 ), which would improve therapy adherence and probably also reduce insecurity, fear, and anxiety in patients, and their relatives.…”
Section: Changes Due To Covid-19 Pandemic In Four Pillars Of Palliatimentioning
confidence: 99%
“…In our study, the students with adequate affirmative gestures did not show a difference in PPI score, but they had better NVS scores. Previous studies revealed that nodding and smiling by the physician were correlated with patient satisfaction and the physician’s perceived friendliness [ 6 , 7 , 13 , 16 ]. Clinicians’ use of gesture can enhance patients’ memory of medical information [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, Mast et al [ 16 ] reported that there was no correlation between looking at a patient’s chart and patient satisfaction. However, in several previous studies, frequent eye contact and less time reading the medical chart improved SP or real patient satisfaction and were associated with higher perceived friendliness and better information recognition [ 6 , 7 , 11 , 13 ]. The SPs of our study might have given more weight to facial expression than eye contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physician caring was operationalized based on Hillen et al [33] who developed, tested, and used doctors’ verbal expressions of caring in a scripted video vignette study to test the effect of caring on trust. These verbal utterances were modified to fit the hemato-oncology setting, based on feedback from the expert panel, the patients, screenwriter, and project group during script development.…”
Section: Methodsmentioning
confidence: 99%